If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -15 = 3x + 40 Reorder the terms: -15 + 6x = 3x + 40 Reorder the terms: -15 + 6x = 40 + 3x Solving -15 + 6x = 40 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -15 + 6x + -3x = 40 + 3x + -3x Combine like terms: 6x + -3x = 3x -15 + 3x = 40 + 3x + -3x Combine like terms: 3x + -3x = 0 -15 + 3x = 40 + 0 -15 + 3x = 40 Add '15' to each side of the equation. -15 + 15 + 3x = 40 + 15 Combine like terms: -15 + 15 = 0 0 + 3x = 40 + 15 3x = 40 + 15 Combine like terms: 40 + 15 = 55 3x = 55 Divide each side by '3'. x = 18.33333333 Simplifying x = 18.33333333
| 5+-1=5t+7 | | x+3x+x+50=180 | | 5a^2-40a+60=0 | | -4=-(1x-8) | | 12+3x=5+4x | | 11=24-8(4-2w) | | 1000=2x^2+2x | | X^2-8x+96=0 | | (y-3)(y+4)=30 | | 180=x+4+3x-9 | | 7x^2+21=28x | | 4x+2x-15=3x+40 | | x+1+3x+1=90 | | 11=24-(4-2w) | | (2+3i)(6-7i)= | | 10+8x=55+3x | | 5x-7-3x=9 | | (9y+1)=(10y-13) | | h=-7.3t^2+8.25t+2.1 | | 2x-3x-464=0 | | -39-12x+7x=46 | | 7x-13+2x+5=180 | | 3x+5x+4-1x+7=88 | | Inx-7=0 | | 2(3x+6)+4(3x+8)=46 | | 11(V+1)-2V=3(3V+1)-7 | | (7x-6)=(8x+5) | | -38=-2(-43d-4) | | 3(n-1)=5n+3(-2n) | | 2x+5+10x-12=90 | | x(3y+2c)= | | (26+7)*3= |